(Dis)Alienating. Implicating. Aesthetics in Love - Stakemeier, Kerstin (The Nordic Journal of Aesthetics, 2025)
The essay is dedicated to understanding aesthetics as a materialist practice committed to disalienation by way of what and who figures as obscene within modern life. It confronts the modern aesthetic subject and its origination in Early Romanticism, with Peter Gorsen’s proposition of a “hermaphroditic eros,” with Kay Gabriel›s “enthusiastic mutuality,” with Michael Löwy’s inquiries into “Romantic Anticapitalism,” and with Frantz Fanon›s insistence on “disalienation.” All to argue that in disalienation aesthetics becomes a work of love without possession.